Impact Analysis of Noise Intensity with Hearing Loss on Laundry Worker - Rindy Astike Dewanty; Sudarmaji Sudarmaji (JURNAL KESEHATAN LINGKUNGAN, 2016)
Abstract: Laundry unit at a hospital can be a source of noise. The impact was very dangerous for workers, especially against hearing. From the results of a preliminary survey of the noise intensity measurements obtained intensity noise of 81.2 dB (A). The purpose of this study was to analyze the effects of noise on hearing loss intensity laundry attendant. This study was an observational with cross sectional design. The instrument used was a questionnaire to see the characteristics of the respondent, sound level meter to measure the intensity of noise and audiometry test to measure the threshold of hearing respondents. The research subject as many as 16 workers of laundry. Based on the results of the study states that 75% of the existing work in the laundry unit has a noise intensity exceeds the required value and 12 officers were on the section. The measurement results with minimum of 65.4 dB (A), to a maximum of 84.0 dB( A) andthe average intensity of noise by 79.04 dB (A). Obtained eight workers (50%) had hearing loss right ear and 6 offi cers (37.5%) had hearing loss left ear. There was a relationship between impaired right ear with noise intensity (Spearman; r = 0.577). The need hearing health for periodic examination least once a year, reducing device noise to keep the noise source, and personal protective equipment (PPE).Keywords: hearing loss, intensity noise, laundry